2020
DOI: 10.7124/bc.000a25
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in expression of S6K1 isoforms in MCF7 cells have a strong impact on the locomotor activity as well as on S6K1 and Akt signaling

Abstract: To generate and characterize MCF-7 cell lines with altered expression of p85, p70 and p60 S6K1 isoforms: p85-/p70-/p60-MCF-7 and p85-/p70-/p60+MCF-7. Methods. CRISPR/ Cas9 gene editing, western blot analysis, immunofluorescence analysis, scratch assay. Results. Modified MCF-7 cells with knocked down expression of p85, p70, p60 or only p85 and p70 S6K1 isoforms were generated. Selective inhibition of only p85 and p70 isoforms in p85-/p70-/p60+MCF-7 cells was accompanied by actin cytoskeleton rearrangements, app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Morphological analysis of tumor cells with altered expression of S6K1 isoforms under 2D and 3D culture conditions. Recently we claimed generation of MCF-7 cells with edited by CRISPR/Cas9 technology expression of p60, p70 and p85 S6K1 isoforms: F1 (p85 -/ p70 + /p60 + ), F2 (p85 -/p70 -/p60 + ), and F3 (p85 -/ p70 -/p60 -) [13,14]. It was demonstrated that alterations in the S6K1 isoforms expression differently affects cell migration [14].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Morphological analysis of tumor cells with altered expression of S6K1 isoforms under 2D and 3D culture conditions. Recently we claimed generation of MCF-7 cells with edited by CRISPR/Cas9 technology expression of p60, p70 and p85 S6K1 isoforms: F1 (p85 -/ p70 + /p60 + ), F2 (p85 -/p70 -/p60 + ), and F3 (p85 -/ p70 -/p60 -) [13,14]. It was demonstrated that alterations in the S6K1 isoforms expression differently affects cell migration [14].…”
Section: Resultsmentioning
confidence: 99%
“…Recently we claimed generation of MCF-7 cells with edited by CRISPR/Cas9 technology expression of p60, p70 and p85 S6K1 isoforms: F1 (p85 -/ p70 + /p60 + ), F2 (p85 -/p70 -/p60 + ), and F3 (p85 -/ p70 -/p60 -) [13,14]. It was demonstrated that alterations in the S6K1 isoforms expression differently affects cell migration [14]. Down regulation of the main S6K1 isoforms p70 and p85 with sustained expression of p60 S6K1 dramatically enhances the locomotor activity of MCF-7 cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations